Production of Limonoids Through Callus and Cell Suspension Cultures of Chinaberry (Melia Azedarach L.) (Bangladesh Journal of Botany, 2021)
To study the in vitro production of limonoid contents through callus and cell suspension cultures of chinaberry (Melia azedarach L.) in different explants were inoculated in Murashige and Skoog (MS) medium for the callus induction with various plant growth regulators (PGRs) separately as well as in combinations. The highest callus induction (73.3%) was observed in nodular stem sections and further callus was subcultured for multiplication and finally transferred to cell suspension medium. The optimized parameters for the production of total limonoids were adjusted and UV-visible spectrophotometer was used to quantify total limonoids at 577 nm. Production of total limonoids through callus cell suspension cultures on the optimized medium was highest (141.7 μg/ml) followed by other sources like KH2PO4 (0.1 g/l) extra supplementation with optimized medium produced (138 μg/ml). Plant callus cell suspension cultures through optimized medium may be considered as a good source for the production of bio-products and its purified form could be used as a medicinal sources.Bangladesh J. Bot. 50(2): 301-309, 2021 (June)